Democratic prospects in Imperial Russia: The revolution of 1905 and the political stock market - Alexander Opitz (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2015)
This paper assesses the attitude of investors towards Democratic change by performing an event study using Russian government bonds. The Revolution of 1905 offers an ideal occasion as, alongside the related revolutionary events, it was accompanied by two opposing constitutional changes within a short period of time. This study contributes to the debate as to whether Imperial Russia could possibly have followed other Western European states, i.e. gradually adopting a democratic rule, or whether a revolution was inevitable - as the writing of Soviet history suggests. Furthermore, the Russo-Japanese War is taken into consideration. The results are basically in line with the literature on the impact of wars on capital markets. Prices of two types of bonds on both the Saint Petersburg and the Berlin stock exchange are employed. As it turns out, investors in the East and West were largely consistent in their reactions.
urn:nbn:de:bsz:100-opus-11714
Keywords: 330; russian economic history; political stock market; Democratic change; impact war on stock markets